Regelung der Längs- und Vertikalbewegung des Linearmotors für ein vollaktives spurgeführtes Bahnfahrzeug - Yang, Bo

Stromrichter- und Regelungskonzepte für Ultraschall-Wanderwellenmotoren - Schulte, T.

Wittgenstein, Ludwig. "Philosophische Untersuchungen. Philosophical Investigations", transl. from the German by G.E.M. Anscombe, edited with a note by Anscombe and R. Rhees, 3rd rev. ed., Blackwell: Oxford 2001, Reprint 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ropolyi, László, “Lakatos and Lukács”, in: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 303–337 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gillies, Donald/Zheng, Yuxin: “Dynamic Interactions with the Philosophy of Mathematics”, In: Theoria. Segunda Epoca 16, No. 42 (2001), 437–459 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Buldt, Bernd u.a. (Hgg.), "Kurt Gödel: Wahrheit & Beweisbarkeit, Bd. 1: Kompendium zum Werk", öbv & hpt: Wien 2002 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tomassi, Paul, “Logic after Wittgenstein”, In: Nordic Journal of Philosophical Logic 6 (2001), 43–70 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lavor, Brendan. "Lakatos. An Introduction", London: Routledge 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mormann, Thomas, “Towards and Evolutionary Account of Conceptual Change in Mathematics: Proofs and Refutations and the Axiomatic Variation of Concepts”, In: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 139–156 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Koetsier, Teun. “Lakatos’ Mitigated Scepticism in the Philosophy of Mathematics”, In: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 189–210 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sundholm, Göran. “Frege, August Bebel and the Return of Alsace-Lorraine: The Dating of the Distinction between Sinn and Bedeutung”, In: History and Philosophy of Logic 22 (2001), 57–73 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Klement, Kevin C., “Russell’s Paradox in Appendix B of the Principles of Mathematics: Was Frege’s response adequate?”, In: History and Philosophy of Logic 22 (2001), 13-28 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Newen, Albert/Nortmann, Ulrich/Stuhlmann-Laeisz, Rainer (Hgg.), "Building on Frege. New Essays on Sense, Content, and Concept", CSLI Publications: Standford, CA 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Takeuti, Gaisi. "Memoirs of a Proof Theorist. Gödel and other Logicians", ed. Mariko Yasugi/Nicholas Passell, World Scientific: New Jersey u.a. 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Martinich, A.P./Sosa, David (Hgg.), "Analytic Philosophy. An Anthology", Blackwell Pubishers: Malden MA 2001 (Blackwell Philosophy Anthologies; 13) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Frischbier, Reinhard. "Kant und die Mathematik", Hallescher Verlag: Halle 2001 (Akademische Studien und Vorträge; 5) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Baker, G.P./P.M.S. Hacker, “Functions in Begriffsschrift”, In: Synthese 135 (2003), 273–297 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Zalta, Edward N., “Fregean Senses, Modes of Presentation, and Concepts”, In: James E. Tomberlin (Hg.), Metaphysics, 2001, Blackwell: Boston 2001 (Philosophical Perspectives; 15), 335–359 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Klein, Carsten, “Conventionalism and Realism in Hans Reichenbach’s Philosophy of Geometry”, In: International Studies in the Philosophy of Science 15 (2001), 243–251 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Uebel, Thomas E., “Carnap and Neurath in exile: Can their disputes be resolved?”, International Studies in the Philosophy of Science 15 (2001), 211-220 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Radu, Mircea, “A Debate About the Axiomatization of Arithmetic: Otto Hölder Against Robert Graßmann”, In: Historia Mathematica 30 (2003), 341–377 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ben-Menahem, Yemima, “Convention: Poincaré and Some of His Critics”, In: British Journal for the Philosophy of Science 52 (2001), 471–513 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dörfler, Willi, „Über die Fiktionalität mathematischer Objekte“, In: Mathematische Semesterberichte 48 (2002), 123–138 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Penco, Carlo, “Frege: TwoTheses, Two Senses”, In: History and Philosophy of Logic 24 (2003), 87–109 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Glock, Hans-Johann (Hg.), "Wittgenstein: a Critical Reader", Blackwell Publishers: Malden, MA 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Zur Konstruktion des Nationalitätenkonflikts im Diskurs (am Beispiel Lemberger Zeitun-gen vom Jahre 1897) - Ptashnyk, Stefaniya (Sprachkontakte in Mitteleuropa)

Murawski, Roman, “Truth vs. Provability - Philosophical and Historical Remarks”, Logic Log. Philos. No. 10 (2002), 93-117 - Peckhaus, Volker (Mathematical Reviews)

Seuren, P.A.M., 2The Logic of Thinking", Koninklijke Nederlandse Akademie van Wetenschappen: Amsterdam 2002 (Mededelingen van de Afdeling Letterkunde, Niewe Reeks, Deel 65, no. 9) - Peckhaus, Volker (Mathematical Reviews)

Newen, Albert/Nortmann, Ulrich/Stuhlmann-Laeisz, Rainer (Hgg.), "Building on Frege. New Essays on Sense, Content and Concept", CSLI Publications: Stanford, CA 2001 - Peckhaus, Volker (Mathematical Reviews)

Rowe, David E., “From Königsberg to Göttingen: a Sketch of Hilbert's Early Career”, In: Math. Intelligencer 25 (2003), 44-50 - Peckhaus, Volker (Mathematical Reviews)

Büttemeyer, Wilhelm (Hg.), "Philosophie der Mathematik", Verlag Karl Alber: Freiburg/München 2003 (Alber-Texte Philosophie; 16) - Peckhaus, Volker (Mathematical Reviews)

Stelzner, Werner, “Compatibility and Relevance: Bolzano and Orlov”, In: Logic and Logical Philosophy Nr. 10 (2002), 137-171 - Peckhaus, Volker (Mathematical Reviews)

Meixner, Uwe (Hg.), "Philosophie der Logik", Verlag Karl Alber: Freiburg/München 2003 (Alber-Texte Philosophie; 19) - Peckhaus, Volker (Mathematical Reviews)

Lernbeobachtungen – Lerndiagnosen. Grundschulunterricht

Beobachten als Aufgabe des Unterrichts - Block, Iris; Kruse , Norbert (Lernbeobachtungen und Lerndiagnosen. Grundschulunterricht)

Lesetagebücher im 2. Schuljahr. Beobachtungen zum frühen literarischen Lernen - Block, Iris (Lernbeobachtungen und Lerndiagnosen. Grundschulunterricht)

Verhüllen und Enthüllen von Wissen und Unwissen in interalloglotter Kommunikation. - Behrent, Sigrid (Enthüllen – Verhüllen. Text und Sprache als Strategie. Beiträge zum XIX. Forum Junge Romanistik, Bochum (11.-14. Juni 2003))

Zur Neurobiologie des Code-Switching. - Behrent, Sigrid; Franceschini, Rita; Reith, Wolfgang; Krick , Christoph (Sociolinguistica: Code switching)

Pedro hat sich verlaufen: Förderung morpho-syntaktischer Sprachfähigkeiten - Albers, Timm (Zeitschrift für Heilpädagogik)

The neurobiology of code-switching: intersentential code-switching in an fMRI-study. - Behrent, Sigrid; Franceschini, Rita; Krick, Christoph; Reith, Wolfgang (Multilingual communication)

Dynamics of the phonon-induced electron transfer between semiconductor bulk and surface states - Zeiser, Andreas; Bücking, Norbert; Götte, Jörg; Förstner, Jens; Hahn, Patrick; Schmidt, Wolf Gero; Knorr, Andreas (physica status solidi (b))
The coupling of surface and bulk states at semiconductor surfaces through electron–phonon interaction is discussed. The governing equations are derived from a microscopic theory in the framework of the density matrix theory. To gain a first insight, model wave functions are used to simulate the dynamics of nonequilibrium electron distributions in three- and two-dimensional states, coupled by Fröhlich interaction. Typical time scales for the coupling are found to be in the order of few hundreds of femtoseconds.

Geschichte der Sieger? Zu Walter Benjamins These von der Parteilichkeit des Historismus - Süßmann, Johannes (De-Marginalisierungen. Geschenkschrift für Gisela Engel zum 60. Geburtstag)

Darstellungsprinzipien in Johannes von Müllers erstem Geschichtswerk - Süßmann, Johannes (Geschichtsschreibung zu Beginn des 19. Jahrhunderts im Umkreis Johannes von Müllers und des Groupe de Coppet. L’historiographie à l’aube du XIXe siècle autour de Jean de Müller et du Groupe de Coppet. Textes allemands réunis par Doris et Peter Walser-Wilhelm. Textes français et édition du volume réalisée par Marianne Berlinger Konqui)
Keywords: Müller; Johannes von; Gatterer; Johann Christoph; Eidgenossenschaft

[Rez. v.] Peter Claus Hartmann (Hg.): Die Mainzer Kurfürsten des Hauses Schönborn als Reichserzkanzler und Landesherren. Bern, Frankfurt/M. 2002 - Süßmann, Johannes (sehepunkte)
Keywords: Schönborn; Johann Philipp von Schönborn; Lothar Franz von Schönborn; Leibniz; Kurmainz; Gesetzgebung; Kulturpatronage

[Rez. v.] Peter Stephan: »Im Glanz der Majestät des Reiches« – Tiepolo und die Würzburger Residenz [...]. Weißenhorn. Anton H. Konrad 2003 - Süßmann, Johannes (sehepunkte)
Keywords: Tiepolo; Giovanni Battista; Würzburger Residenz; Reichsidee

Elterliche Prädiktoren für die Ablehnung von Schullaufbahnempfehlungen - Bloh, Bea; Schürer, Sina; van Ophuysen, Stefanie

Erwartungen an die weiterführende Schule: empirische Untersuchung zu den Übergangserwartungen von Grundschüler/innen - Leffelsend, S.; Bloh, Bea (Empirische Pädagogik)

Narrativising the Body: Fragmentation and Unification in Jed Mercurio’s 'Bodies' - Mildorf, Jarmila (Interdisciplinary Perspectives on Health, Illness and Disease)

Narratives of Domestic Violence Cases: GPs Defining their Professional Role - Mildorf, Jarmila (Making Sense of Health, Illness and Disease)

Book review: Vera and Ansgar Nünning (eds) (2002). Erzähltheorie transgenerisch, intermedial, interdisziplinär. Trier: WVT. / Ansgar and Vera Nünning (eds) (2002). Neue Ansätze in der Erzähltheorie. Trier: WVT - Mildorf, Jarmila (Narrative Inquiry)

Data Compression for Multiple Scan Chains Using Dictionaries with Corrections - Wuertenberger, Armin; S. Tautermann, Christofer; Hellebrand, Sybille (IEEE International Test Conference (ITC'04))

“Wir nähern uns dem Zeitalter der Massenpolitik.” – Bertolt Brechts dialektisch-experimentelle Vorführung des “öffentlichen Zustands” im Dreigroschenprozeß - van Laak, Lothar (Sprachen des Politischen. Medien und Medialität in der Geschichte)

Literarisches Wahrnehmen – ästhetisches Handeln. Zum Stellenwert der Aufmerksamkeit im Prozeß der Aisthesis - van Laak, Lothar (Wahrnehmen und Handeln. Perspektiven einer Literaturanthropologie)

Wendungen der Gelehrsamkeit – Raoul Schrotts Tropen - van Laak, Lothar (Die eigene und die fremde Kultur. Exotismus und Tradition bei Durs Grünbein und Raoul Schrott)

‘Popularität’ als Antiklassizismus in Christoph Martin Wielands Don Sylvio von Rosalva und Musarion - van Laak, Lothar (Baden – Württemberg – Polen. Germanistische Annäherungen)

“Dichterisches Gebilde” und Erlebnis. Überlegungen zu den Beziehungen zwischen Wilhelm Dilthey und dem George-Kreis - van Laak, Lothar (George-Jahrbuch 5 (2004/2005))

Standardisiert die Bildungsstandards! Eine Stellungnahme zu den Entwürfen der nationalen Bildungsstandards für den Mittleren Schulabschluss in den Fächern Biologie, Chemie und Physik - Kullmann, Harry

Hügelkette-huldvoll - Elit, Stefan (Goethe-Wörterbuch 4,12)

infundieren-inhaftieren - Elit, Stefan (Goethe-Wörterbuch 4,12)

Hypostasis-Hysteron - Elit, Stefan (Goethe-Wörterbuch 4,12)

Ih-ihroseits - Elit, Stefan (Goethe-Wörterbuch 4,12)

[Doppelrezension:] Johann Karl Wezel (1747-1819), hg. v. Alexander Košenina u. Christoph Weiß, St. Ingbert 1997 (Literatur im historischen Kontext. Studien und Quellen zur deutschen Literatur- und Kulturgeschichte vom 18. Jahrhundert bis zur Gegenwart 2); Michael Hammerschmidt:Skeptische Poetik in der Aufklärung. Formen des Widerstreits bei Johann Karl Wezel, Würzburg 2002 (Epistemata. Würzburger wissenschaftliche Schriften; Literaturwissenschaft 411) - Elit, Stefan (JbIG 36, H. 2 (Jahrbuch für brandenburgische Landesgeschichte))

Franz Witek: Die "Bühne des Schicksals". Demetrios von Makedonien in Historiographie und Drama, Horn/Wien 2001 (Musae Benedictinae Salisburgenses 1) - Elit, Stefan (NlatJb 6)

Sangspruchtradition. Aufführung – Geltungsansprüche – Spannungsfelder

„Grenzüberschreitungen: Strukturen des Übergangs im ‚Wilhelm von Österreich‘“ - Egidi, Margreth (Würzburg, der Große Löwenhof und die deutsche Literatur des Spätmittelalters (Imagines medii aevi 17))

„Der performative Prozess. Versuch einer Modellbildung am Beispiel der Sangspruchdichtung“ - Egidi, Margreth (Sangspruchtradition. Aufführung – Geltungsstrategien – Spannungsfelder (Kultur – Wissenschaft – Literatur 5))

„Einleitung“ - Egidi, Margreth; Mertens, Volker; Miedema, Nine (Sangspruchtradition. Aufführung – Geltungsstrategien – Spannungsfelder (Kultur – Wissenschaft – Literatur 5))

Evidence for split foci of attention in a priming paradigm. - Scharlau, Ingrid (Perception & Psychophysics)
Most models of visuospatial attention include the notion that attention is dedicated to a single location in space. However, several researchers have found evidence that under appropriate circumstances, attention may be allocated to noncontiguous locations (e.g., Awn & Pashler, 2000; Bichot, Cave, & Pashler, 1999; Kramer & Hahn, 1995). In the present experiments, the spatial distribution of attention was assessed by a novel method, perceptual latency priming: the latency benefit of an attended visual stimulus, as compared with a nonattended stimulus. Experiment 1 assessed whether observers are able to attend to two nonadjacent regions or a region of variable size. Experiment 2 tested whether, when two distant locations are attended to, the region between them is necessarily also in the focus of attention. Two further experiments controlled for objections against the method used and replicated the main results of the first two experiments. The experiments showed a robust attentional pr
Keywords: visuospatial attention; priming paradigm; spatial distribution; Adult; Attention; Female; Humans; Male; Attention; Priming; Spatial Perception; Visuospatial Ability

Illusory line motion and perceptual latency priming: Two alternative measures for attentional facilitation - Scharlau, Ingrid (Dynamic Perception 2004: Workshop of GI section 1.0.4 "Image Understanding" and the European Networks MUHCI and ECOVISION)

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

The spatial distribution of attention in perceptual latency priming. - Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology A: Human Experimental Psychology)
The spatial distribution of visual attention is a yet unresolved question. One of the main topics is whether attention is distributed in a graded fashion around an attended location (e.g., Downing, 1988; Zimba & Hughes, 1987). The present experiments explore whether, and on which conditions, gradients of attention arise and contribute to perceptual facilitation. A masked or unmasked prime precedes one of two targets whose temporal order has to be judged. The prime captures attention, which shortens the perceptual latency of the primed target (perceptual latency priming; Scharlau & Neumann, 2003a; Shore, Spence, & Klein, 2001). No strong evidence for an attentional gradient was found. (1) Accuracy of temporal order judgements was independent of the distance between the two targets that were judged. That is, facilitation of the second target by the first target was spatially invariant. (2) With targets of short duration, facilitation was independent of prime-target distance. (3) With ta
Keywords: visual attention; spatial distribution; perceptual latency priming; Attention; Priming; Spatial Organization; Visual Perception

Advanced Hysteresis Control of Brushless DC Motors - Böcker, Joachim (German-Korean Symposium 2004 on Power Electronics and Electrical Drives, Aachen)
Brushless DC motor drives are typically employed in speed controlled applications. Torque control, particularly during regenerative mode, is not the standard domain of BLDC drives. However, it can be shown that the known BLDC control approach can be extended to control the torque in the regenerative mode even for low speed or at standstill. A hysteresis controller is proposed, which is specified by means of a state chart.

Child-parent relationships - Noack, Peter; Buhl, Heike M. (Growing together. Personal relationships across lifespan)
The chapter gives an overview on the development of the relationships of parents and their offspring. While the selection of issues addressed is not meant to be comprehensive, the chapter focuses on conceptualizations and findings of particular relevance: Individuality and relatedness, the active role that parents and their offspring play in shaping their relationship, the importance of a biographical perspective on relationship development, and contextual influences on child-parent relationships. The chapter concludes with consideration of directions for future research. Child-parent relationships are special. This is obviously true on an individual level. For example, children see their parents as outstanding people - at least up until the transition to adolescence. Likewise, some parents are infatuated with their children and expect much of their sons and daughters, sometimes to the point of overtaxing their abilities and patience. At the same time, child-parent relationships, in general, have features that give them a particular significance. As compared to other types of relationships, bonds between parents and their offspring are of an extremely long-standing nature. Moreover, when parents and children interact, aspects of socialization and education tend to play a more important role than is the case among siblings, friends, or romantic partners. Finally, it has to be recognized that child-parent relationships represent an intergenerational constellation. Relationships between children and parents surpass most other relationships in duration. We take Germany as a case in point.

Relations with parents and friends during adolescence and early adulthood - Noack, Peter; Buhl, Heike M. (Marriage and Family Review)
Relative power, conflict, and intimacy in adolescents' and young adults' relations with mothers, fathers, and best friends were examined. Two hundred eighty-five students from German high-track (i.e., university bound schools 6th, 9th, 12th grade), undergraduate and graduate students completed the respective scales of the Network of Relationships Inventory (Furman & Buhrmester, 1985). Relations with friends were more symmetrical and had a better socio-emotional quality than relations with parents. Still, increases in relative power in relations with parents were accompanied by low absolute levels of conflict. A symmetrical distribution of power in the family was not reached before the end of the third decade of life. To explore the influence of the entry into worklife on close relations, an additional subsample of 55 working young adults was compared with the participating university students. Despite slight differences in age-related patterns of intimacy, similarities prevailed. Overall, findings mostly converge with observations in U.S. samples of high school and college students and point to a more general process of relationship development as suggested by individuation theory.

Um/Ordnungen des Ornamentalen in der Moderne. Flugbilder bei Gertrude Stein, Lászlò Moholy-Nagy und Ernst Jünger. - Öhlschläger, Claudia (Inszenierungen in Schrift und Bild)

Galanterie als kulturelle Identitätsbildung: Französisch-deutscher Kulturtransfer im Zeichen der Querelles (Dominique Bouhours – Christian Thomasius – Benjamin Neukirch) - Steigerwald, Jörn (German Literature, History and the Nation. Papers from the Conference ‘The fragile Tradition’ Cambridge 2002, Volume 2)

Le baiser galant: approche d’une configuration érotique de l’esthétique galante - Steigerwald, Jörn (Les baisers des lumièresc)

Lemma Kulturtransfer - Steigerwald, Jörn (Metzler Lexikon Literatur- und Kulturtheorie, Stuttgart/Weimar 20012, S. 353; Stuttgart/Weimar 2004, S. 367-377 .Erneut veröffentlicht in: Ansgar Nünning (Hg.): Grundbegriffe der Kulturtheorie und Kulturwissenschaften. Stuttgart 2005, S. 124-125)

Encyclopédie der Sexualpathologie - Steigerwald, Jörn (Sexualität und Imagination. Pathologien der Einbildungskraft im medizinischen Diskurs der Frühen Neuzeit)

Sexualität und Imagination. Pathologien der Einbildungskraft im medizinischen Diskurs der Frühen Neuzeit

Story und History – „Nation-Writing“ in Emine Sevgi Özdamars Das Leben ist eine Karawanserei - Zierau, Cornelia (Die andere Deutsche Literatur)

Bericht über eine Studienreise - Zierau, Cornelia (Alman Dili ve Edebiyatı Dergisi - Studien zur Deutschen Sprache und Literatur No. XV. İstanbul: İÜ Edebiyat Fakültesi (Hg.: Abteilung für deutsche Sprache und Literatur an der Philosophischen Fakultät der Universität İstanbul))

Specification and Formal Verification of Temporal Properties of Production Automation Systems - Flake, Stephan; Müller, Wolfgang; Pape, Ulrich; Ruf, Jürgen (Integration of Software Specification Techniques for Applications in Engineering)
This article describes our approach for the specification and verification of production automation systems with real-time properties. We focus on the graphical MFERT notation and RT-OCL (Real-Time Object Constraint Language) for the specification of state-oriented real-time properties. RT-OCL is an extension of the Object Constraint Language (OCL) that is part of the Unified Modeling Language (UML). We introduce the formal semantics of RT-OCL based on a formal model of UML Class and State Diagrams and provide a mapping to temporal logics. The applicability of our approach is demonstrated by the case study of a manufacturing system with automated guided vehicles.
Keywords: Model Check; Temporal Logic; Object Constraint Language; Abstract Syntax; Temporal Logic Formula

Workflow Management Middleware for Secure Distance-Spanning Collaborative Engineering - Schattkowsky, Tim; Müller, Wolfgang; Pawlak, Adam (Workflow Handbook 2004)

Refinement of Finite State Machines with Complementary Model Checking - Krupp, Alexander; Müller, Wolfgang (UML-B System Specification for Proven Electronic Design)

Combining Formal Refinement and Model Checking for Analysis of Realtime Systems - Krupp, Alexander; Müller, Wolfgang; Oliver, Ian (Best of FDL'03)

The Echo Cancellation Unit Case Study - Krupp, Alexander; Müller, Wolfgang; Oliver, Ian (UML-B System Specification for Proven Electronic Design)

Innovative Warmumformung - Tröster, Thomas; Rostek, W. (Neuere Entwicklungen in der Blechumformung : [Vortragstexte zur Veranstaltung Internationale Konferenz "Neuere Entwicklungen in der Blechumformung" in Fellbach)

Director reorientation of a side-chain liquid crystalline polymer under extensional flow - Cormier, Ryan J.; Schmidt, Claudia; Callaghan, Paul T. (Journal of Rheology)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

A new approach to lamellar phases (Lα) in water – non-ionic surfactant systems - Stubenrauch, C.; Burauer, S.; Strey, R.; Schmidt, Claudia (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Texttypen und Diskurse in Zusammenhängen sprachlicher Identitätskonstruktion. Überlegungen im Anschluss an Foucault - Tophinke, Doris (Fliegende Bilder, fliehende Texte)

Quatschwörterverse und Satzklötze. Sprachförderung im Kindergarten - Tophinke, Doris (Infodienst. Kulturpädagogische Nachrichten)

The Selfexplication of Thinking through AI - Hagengruber, Ruth Edith (Philosophy and Informatics: Philosophy and Artificial Intelligence)

Das Unsichtbare sichtbar machen. Die soziale Wirklichkeit und ihre Grundlagen in der Philosophie von Edith Stein - Hagengruber, Ruth Edith (Edith Stein Jahrbuch)

Ontologische Strukturen. Gegenwärtige Tendenzen und ihre Anwendung in der Wirtschaftsinformatik - Hagengruber, Ruth Edith (Wissenschaftstheorie in Ökonomie und Wirtschaftsinformatik. Theoriebildung und –bewertung, Ontologien, Wissensmanagement)

Vom Besonderen zum Allgemeinen – zu einer Neuorientierung im Verhältnis von Philosophie, Wissenschaft und Feminismus - Hagengruber, Ruth Edith (Philosophinnen im 3. Jahrtausend. Ein Einblick in aktuelle Forschungsfelder)

„Liebe geht durch den Magen“: Mahlzeit und Familienglück im Strom der Zeit - Schlegel-Matthies, Kirsten (Die Revolution am Esstisch. Neue Studien zur Nahrungskultur im 19./20. Jahrhundert)

L’intercession dans les relations politiques au Moyen Age classique - Kamp, Hermann (L’intercession du Moyen Age au Temps modernes)

Performing post / trans / techno / queer. Pluralisierung als Selbst- und Machttechnologie - Weber, Jutta (Gender Studies: Standorte – Zukunftsräume)

Wir sind immer mittendrin? Transdisziplinarität in der feministischen Natur- und Technowissenschaftsforschung - Weber, Jutta; Saupe, Angelika (Dokumentation 29. Kongreß von Frauen in Naturwissenschaft und Technik)